Using Kotter's Change Model for Implementing Bedside Handoff: A Quality Improvement Project. Issue 4 (October 2016) - Small, Alison; Gist, Diana; Souza, Danielle; Dalton, Joanne; Magny-Normilus, Cherlie; David, Daniel
Abstract : Supplemental Digital Content is Available in the Text.